Using fluorescent lipids contributes to the active learning of principles underlying lipid signaling - Peppino Margutti, Micaela Yesica (2018)
The concepts of phospholipase activity is often taught in undergraduate biology and biochemistry classes and reinforced in laboratory exercises. However, very rarely does the design of these exercises allow students to directly gain experience in the use of modern instruments such as digital imaging systems and fluorescence spectrophotometers. The laboratory exercise described here involves the use of fluorescent lipids to evaluate phospholipase activity. Students use thin layer chromatography (TLC) to understand how lipids change under different conditions (i.e. abiotic and biotic stress). They explore strategies to separate, visualize and quantify lipids by TLC, digital imaging, and fluorometry. They also have increased opportunities for hands‐on practise with experimental design, liposome sample preparation, and implementation of instrumentation commonly used by experienced researchers; all while learning and applying fundamental concepts about lipids.